Penyuluhan dan Pendampingan Penataan Lingkungan Pada Permukiman Kumuh di Kelurahan Bontorannu, Kecamatan Mariso, Kota Makassar - Mimi Arifin; A. Yudhono; S. Wunas; Y. Jinca; Arifuddin Akil A.R.Rasyid; I. Latief; M. Ali; F. Azmy; Y.K. Dewi; W.W. Osman; S.A. Ekawati; S. Wahyuni; L.M. Asfan; G. Lakatupa; S. Trisutomo (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
Dense settlements on the outskirts of Jongaya Canal, Bontorannu Urban Village, are one of the causes of the pollution of the Losari beach environment as a landmark in Makassar. The accumulation of rubbish along the canal further strengthens people's behavior in disposing garbage in the canal. The Bontorannu urban area has several potentials that can be used as supporting factors in revitalization efforts, namely canals that can be used as water transportation because the Jongaya canal can be connected to Losari Beach and surrounding islands. As a fisherman settlements located in urban area and also in a strategic area of a coastal corridor that has more value as an Integrated Business and Tourism Center (Makassar City RTRW 2015-2034), it certainly becomes an attraction. The purpose of community dedication is to 1) Identify the characteristics of the infrastructure of community settlements and the community's preference for the condition of the edge of the Jongaya Canal settlement in the Bontorannu Village, Mariso District, Makassar City. 2) Arranging the direction of environmental structuring in slums in Bontorannu Sub-district Mariso District Makassar City based on community. The method used is a focus group discussion (FGD) to get input on the needs and problems in their environment as well as providing appropriate stimulus to the community so that community perceptions and proposals for handling problems with the environment and settlement conditions are as expected. Recommended directions for dealing with settlement conditions include: procurement of street lights, addition of trash bins in each corridor and canal edge, land acquisition in RW 1, RW 2, RW 3, and RW 4 to open road access, provide parking area for tourists who come to visit, as well as the desire of the community to sell culinary, souvenirs, and making photo spots to attract tourists to increase the community economy.